MARKETING MIX ANALYSIS BUSINESS SUCCESS CEREMONIAL MEANS FIBER-BASED IN BRESELA VILLAGE, GIANYAR - Handayani, Made Mulia; Mandiyasa, I Kadek Sara; Arini, Ida Ayu (ADI Journal on Recent Innovation, 2020)
Bresela village is a business center for fiber ceremony facilities in Gianyar district. The success of the business in the village of Bresela is influenced by several factors, one of which is marketing mix. The purpose of this study was to determine the business development of fiber-based ceremonial facilities in Bresela Village and to analyze the implementation of Maketing Mix in the success of the business. This research is qualitative research with data collection techniques through observation, interviews and documentation studies. Determination of informants in this study using purposive sampling technique and using data triangulation techniques. The results of the study explained that the business development of fiber-based ceremonial facilities in Bresela Village has increased in terms of the number of businesses, profitability, total production, market share and an increase in the number of workers. Marketing implementation means in the business success of fiber-based ceremonial facilities in Bresela Village through the aspects of product, price, place and promotion can increase sales volume so that it determines business success.